2007
DOI: 10.1074/jbc.m705349200
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of p53 in Human Cytomegalovirus-initiated Cells Is Associated with Sequestration of HDM2 and Decreased p53 Ubiquitination

Abstract: Human cytomegalovirus (HCMV) induces serum-or densityarrested human lung (LU) cells to traverse the cell cycle, providing it with a strategy to replicate in post-mitotic cells that are its cellular substrate in vivo. HCMV infection also induces high cellular levels of p53, seemingly in contradiction to the observed cell cycle progression. This study was undertaken to examine the mechanism(s) of the increased p53 abundance. HCMV infection caused a 4-fold increase in p53 that preceded a substantial increase in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 70 publications
(75 reference statements)
9
45
2
Order By: Relevance
“…However, our data showed that both proteins are drastically stabilized in cells treated with MG132, suggesting that transcriptional repression might only IE2-86 protein binds Mdm2 and seems to facilitate its degradation in a proteasome-independent manner. 28 In another study, Chen et al showed that Mdm2 was downregulated in HCMVinfected cells, and its abundance was only slightly restored in the presence of proteasome inhibitor MG132, 29 a phenomenon similar to what we have observed with HAdV-infected cells (Fig. 4).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, our data showed that both proteins are drastically stabilized in cells treated with MG132, suggesting that transcriptional repression might only IE2-86 protein binds Mdm2 and seems to facilitate its degradation in a proteasome-independent manner. 28 In another study, Chen et al showed that Mdm2 was downregulated in HCMVinfected cells, and its abundance was only slightly restored in the presence of proteasome inhibitor MG132, 29 a phenomenon similar to what we have observed with HAdV-infected cells (Fig. 4).…”
Section: Discussionsupporting
confidence: 68%
“…27 Although this epidemiological finding awaits experimental validation, it seems that increased Mdm2 expression might confer resistance to HPV infection, thereby reducing the risk of OSCC. Downregulation of Mdm2 has been observed in cells infected with human cytomegalovirus (HCMV) 28,29 and HAdVs. 9 Downregulation of Mdm2 could be due to inactivation and destruction of p53 in HAdV-infected cells, as Mdm2 gene expression is activated by p53.…”
Section: -35mentioning
confidence: 99%
“…Furthermore, many reports have described a viral connection between TP53 and cell cycle arrest. Herpesviruses, such as herpes simplex virus (40), human herpesvirus 6 (41), and human cytomegalovirus (42)(43)(44), cause cell cycle arrest via the TP53 pathway; however, the viral proteins responsible for TP53 stabilization and the precise mechanisms and significance of cell cycle arrest remain unknown. The data in this study might provide a clue to the mechanism and the significance of cell cycle arrest induced by these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome-mediated Degradation of p53 Was Inhibited in IAV-infected Cells-Previous studies demonstrated that the increase in p53 protein in IAV-infected cells was independent of increased transcription (4,11) and it is known that certain types of viral infection affect the stability of p53 protein (26,27). Therefore, in this study, we analyzed p53 stability in IAV-infected cells.…”
Section: Accumulation and Activation Of P53 Protein In Iav-infected Cmentioning
confidence: 99%
“…ibly disrupts Mdm2-p53 protein complexes (27,31), and measured its effect on p53 ubiquitination in mock-and IAV-infected cells. The ladders of polyubiquitinated p53 were detected in mock-infected cells in the presence of MG132 (Fig.…”
Section: Accumulation and Activation Of P53 Protein In Iav-infected Cmentioning
confidence: 99%